The timing of pediatric epilepsy syndromes: What are the developmental triggers?. (November 2013) - Paolicchi, Juliann M.
Abstract : Pediatric epilepsy is characterized by multiple epilepsy syndromes with specific developmental triggers. They initiate spontaneously at critical periods of development and can just as spontaneously remit. Accompanying neurocognitive disabilities are often specific to the epileptic syndrome. Infantile or epileptic spasms have a very specific developmental window in the first year of life. Preceding the epilepsy, developmental arrest is common. The neurologic pathways underlying the development of spasms have been identified through PET scans as developmental abnormalities of serotonergic and GABAergic neurotransmitter systems in the brain stem and basal ganglia. Childhood absence epilepsy (CAE) and benign centrotemporal epilepsy syndrome (BECTS) are both known genetic epilepsy syndromes; they have a discrete onset in childhood with remission by puberty. In CAE, disturbances of specific calcium channels at key developmental stages lead to aberrant disruption of thalamocortical synchrony. Similarly, a complex interplay between brain development, maturation, and susceptibility genes underlies the seizures and the neurocognitive deficits of BECTS.